Combination therapy with immune check point inhibitors and acute kidney injury. (1st February 2023) - Valentin, Amalie; Møller, Anne Kirstine Hundahl; Palshof, Jesper Andreas; Broberg, Bo; Gravesen, Eva; Svane, Inge Marie; Hansen, Ditte
Abstract: Background: Immune checkpoint inhibitors have revolutionized the treatment of metastatic renal cell carcinoma and malignant melanoma but are also associated with a risk of severe side effects. Nephrotoxicity is an immune checkpoint inhibitor-related adverse effect, but acute kidney injury (AKI) can also be caused by other more common conditions. This study aimed to describe the incidence and causes of AKI in patients treated with combination therapy of immune checkpoint inhibitors. Material and methods: This retrospective cohort study included 200 patients receiving ipilimumab and nivolumab for either metastatic renal cell carcinoma or malignant melanoma at the Department of Oncology at Copenhagen University Hospital, Herlev between 1 January 2019 and 31 December 2020. The incidence and cause of AKI within 6 months after treatment was determined. Results: In the 96 patients treated for malignant melanoma 15 patients (16%) had an episode of AKI. Two of these patients had potential immune checkpoint inhibitor-related AKI both of which received treatment with a proton pump inhibitor (PPI). Of the 104 included patients with metastatic renal cell carcinoma 26 patients (25%) developed AKI. Five of these patients had potential immune checkpoint inhibitor-related AKI. Treatment with PPI before the development of AKI occurred in 4 out of these 5 patients. Conclusion: Patients receiving combination therapy with checkpoint inhibitors are at high risk of AKI, but different causes of AKI should always be considered. Use of PPI concurrently with ICIs is likely to increase the risk of AKI.